2005
DOI: 10.1177/0021998305050430
|View full text |Cite
|
Sign up to set email alerts
|

Interaction between Cracking and Oxidation in Organic Matrix Composites

Abstract: The thermal oxidative degradation of carbon fiber/bismaleimide (Hexel T800H/F655-2) and carbon fiber/amine-cross-linked epoxy (Cytec Fiberite IM7/977-2) unidirectional composites and their corresponding neat polymers has been studied in air at temperatures ranging from 150 to 240 C by optical microscopy, using an interferential contrast, and IR microspectrophotometry.A coarse analysis of the damaged zone allowed the determination of main kinetic characteristics in the whole degradation process (oxidation, crac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
36
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 74 publications
(37 citation statements)
references
References 22 publications
1
36
0
Order By: Relevance
“…Colin et al (2005) showed that such models can also be used to predict oxygen diffusivity in composites. More recently, roy and Singh (2009) showed that these models can be improved to take into account physical discontinuities such as highly permeable fi bre/matrix interface or fi bre/matrix debonding due to oxidative shrinkage and erosion.…”
Section: 6mentioning
confidence: 99%
See 1 more Smart Citation
“…Colin et al (2005) showed that such models can also be used to predict oxygen diffusivity in composites. More recently, roy and Singh (2009) showed that these models can be improved to take into account physical discontinuities such as highly permeable fi bre/matrix interface or fi bre/matrix debonding due to oxidative shrinkage and erosion.…”
Section: 6mentioning
confidence: 99%
“…Degradation gradients, resulting from diffusion control of chemical reaction kinetics, play an important role from a mechanical point of view. Schematically, an initially ductile/tough and homogeneous polymer sample is progressively transformed into a binary structure, the sample core remaining ductile/tough, whereas the superficial layer becomes brittle and thus highly sensitive to cracking (Colin et al, 2005). A superficial crack can rapidly cross the whole superficial layer thickness and reach the skin−core interface.…”
Section: Oxidation-induced Spontaneous Crackingmentioning
confidence: 99%
“…While the time-dependent physical, chemical, and damage-induced degradation mechanisms have been studied for some resin systems, polymer composite thermal oxidation studies from a mechanistic perspective are nascent. Notable exceptions to this are the recent works of Colin and Verdu [1], Colin et al [2], Wang and Chen [3], Pochiraju and Tandon [4], Tandon et al [5], and past work by Skontorp et al [6], Wise et al [7], and McManus et al [8]. Equally important are the experimental characterization efforts by such groups as Bowles et al [9], Tsuji et al [10], Abdeljaoued [11], and Schoeppner et al [12].…”
Section: Introductionmentioning
confidence: 96%
“…The thermo-oxidative degradation occurs initially at the outer surface of the composite and proceeds inwards via a diffusion mechanism [8][9][10]. Simultaneously, microcracks may occur due to the mismatches in the coefficients of thermal expansion between the fibers and matrix, as well as the resin shrinkage [11] caused by the thermo-oxidative aging (TOA).…”
Section: Introductionmentioning
confidence: 99%